103k views
0 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the second equation is substituted into the first equation.

2x − 7y = 4
3x + y = −17

A) 2(3x − 17) − 7y = 4
B) 2(−3x − 17) − 7y = 4
C) 2x − 7(3x − 17) = 4
D) 2x − 7(−3x − 17) = 4

User OnkarDhane
by
4.9k points

2 Answers

2 votes

Answer:

The correct answer is D.

Explanation:

I got it correct on the test. I hope this helps!

If you were to use the substitution method to solve the following system, choose the-example-1
User Tony Ju
by
5.3k points
5 votes

Answer:

option D

2x − 7(−3x − 17) = 4

Explanation:

Given in the question two equations

Equation 1

2x - 7y = 4

Equation 2

3x + y = -17

Rearranging equation 2 in terms of y

3x + y = -17

y = -17 - 3x

Put this value of y in Equation 1

2x - 7y = 4

2x - 7(-17 - 3x) = 4

So,

If you use the substitution method to solve the following system, new equation will be

2x - 7(- 3x - 17) = 4

User Steven Pessall
by
5.2k points